Distribution by provenance and altitude of the RS5522 polymorphism of the NR3C2 mineralocorticoid receptor gene in Peruvian populations - Marcos-Carbajal, Pool (2024)
Objective: Determine the distribution of the RS5522 polymorphism of the mineralocorticoid receptor gene NR3C2 according to its origin and altitude in Peruvian populations. Materials and methods: After signing the informed consent, adults from Lima (22), Ica-Chincha (14), Lambayeque-San José (16) participated; Puno-Uros (10), Puno-Taquile (6), Puno-Amantani (6), Arequipa-Chivay (10), Arequipa-Cabanaconde (6), Ancash-Parobamba (20), Apurímac-Andahuaylas (10), Apurímac-Abancay (10), Cajamarca-Puentecillos (13), Cajamarca-Ichocan (7), Loreto-Andoas (16), and San Martín-Lamas (22). Epidemiological and geographical data, biological blood sample and/or oral swab were collected. DNA extraction was performed using a standard technique. The determination of the RS5522 polymorphism was by real-time PCR. Variables were categorized by origin, geographic region (coast, mountains or jungle), and altitude (<2500 meters above sea level or ≥2500 meters above sea level). The Hardy Weimberg statistical test and Pearson's X2 test were applied, with a p value <0.05 being significant for a 95% CI. Results: A high frequency of the RS5522 variant of the NR3C2 gene was present in Peruvian populations. The distribution ranges in the Coast, Sierra and Jungle, respectively, were 78.57-87.50%, 50.00-93.75%, and 75.00-93.18%. According to the altitude, the distribution range at <2500 masl was 75.00-93.18%, and ≥2500 masl was 50.00-93.75%. Conclusions: A heterogeneous distribution of the genetic variant was observed among the Peruvian subpopulations studied, apparently being greater for those located in the mountain region and at ≥2500 meters above sea level. It should be noted that the genetic variant studied encodes a protein with an important physiological role. and also as a target for drugs.